Barriers to healthcare: Instrument development and comparison between autistic adults and adults with and without other disabilities. (November 2017) - Raymaker, Dora M; McDonald, Katherine E; Ashkenazy, Elesia; Gerrity, Martha; Baggs, Amelia M; Kripke, Clarissa; Hourston, Sarah; Nicolaidis, Christina
Our objective was to use a community-based participatory research approach to identify and compare barriers to healthcare experienced by autistic adults and adults with and without other disabilities. To do so, we developed a Long- and Short-Form instrument to assess barriers in clinical and research settings. Using the Barriers to Healthcare Checklist–Long Form, we surveyed 437 participants (209 autistic, 55 non-autistic with disabilities, and 173 non-autistic without disabilities). Autistic participants selected different and greater barriers to healthcare, particularly in areas related to emotional regulation, patient-provider communication, sensory sensitivity, and healthcare navigation. Top barriers were fear or anxiety (35% (n = 74)), not being able to process information fast enough to participate in real-time discussions about healthcare (32% (n = 67)), concern about cost (30% (n = 62)), facilities causing sensory issues 30% ((n = 62)), and difficulty communicating with providers (29% (n = 61)). The Long Form instrument exhibited good content and construct validity. The items combined to create the Short Form had predominantly high levels of correlation (range 0.2–0.8, p < 0.001) and showed responsiveness to change. We recommend healthcare providers, clinics, and others working in healthcare settings to be aware of these barriers, and urge more intervention research to explore means for removing them.